MOVPE growth of thick (∼1 µm) InGaN on AlN/Si substrates for InGaN/Si tandem solar cells. (21st July 2015) - Yamamoto, Akio; Kodama, Kazuki; Hasan, Md. Tanvir; Shigekawa, Naoteru; Kuzuhara, Masaaki
Abstract: In order to develop key technologies for InGaN/Si two-junction tandem solar cells, MOVPE growth of thick InGaN on Si p-on-n cell structures has been studied. By clarifying the phase separation behavior of MOVPE InGaN, a thick (∼1 µm) In x Ga1− x N ( x ∼ 0.5) without phase separation is successfully grown on AlN/Si(111) wafers. A sufficient current flow for the operation of the tandem cell is obtained through n-InGaN/AlN/p-Si structures by employing the annealing of AlN/Si wafer at around 1000 °C in NH3 flow just before InGaN growth. The annealing of AlN/Si wafers also brings about the degradation of the underlying Si pn junction. The optimization of the annealing conditions is required to balance such favorable and unfavorable effects.